2018
DOI: 10.1002/pat.4411
|View full text |Cite
|
Sign up to set email alerts
|

Diphase flame‐retardant effect of ammonium polyphosphate and dimethyl methyl phosphonate on polyisocyanurate‐polyurethane foam

Abstract: Building energy consumption is an important component in the total social energy consumption. How to reduce building energy consumption became an important issue in today's society. Therefore, building insulation materials, as a kind of effective energy saving method, has been widely used for the external walls. However, the occurrence of many building fires caused by the ignition of the flammable insulation materials has brought serious damage to people. Consequently, it is significant to develop insulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Comparing with the reactive flame retardant, the addition flame retardant is easier to prepare by physical methods and more cost‐favored. For example, ammonium polyphosphate (APP) as the representative of the addition flame retardant has been applied into polyurethane foam due to its high contents of phosphorus, smaller loadings, and low cost . However, the poor dispersibility and compatibility of APP negatively impact the property of RPUF .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing with the reactive flame retardant, the addition flame retardant is easier to prepare by physical methods and more cost‐favored. For example, ammonium polyphosphate (APP) as the representative of the addition flame retardant has been applied into polyurethane foam due to its high contents of phosphorus, smaller loadings, and low cost . However, the poor dispersibility and compatibility of APP negatively impact the property of RPUF .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the LOI value of RPUF, it is necessary to combine MAPP with other flame retardants for enhancing the gas‐phase flame retardant effect in the earlier stage of combustion. Dimethyl methylphosphonate (DMMP) is a kind of liquid phosphorus‐containing flame retardant with high efficiency, which has been used in polyurethane foams by a lot of researchers . It is found that DMMP can release the PO·and PO 2 ·free radicals in the early stage due to the lower thermal degradation temperature .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Derivative incorporating secondary amines yielded phosphonamidates that were applied as FR in polyurethanes [27]. Phosphonates with intermediate oxidation state of +III, e.g., diethyl ethylphosphonate (DEEP) and dimethyl phenylphosphonate (DMPP) have been established as halogen-free FRs for polyurethanes, polyesters, and polyamides [28]. In all cases, the P-containing compounds were applied as non-reactive FR.…”
Section: Introductionmentioning
confidence: 99%